HUMAN CONCEPT OF THE ENVIRONMENT AND THE UNIVERSE PERSPECTIVE OF THE QURAN - Tian Khusni Akbar; Mhd. Lailan Arqam (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
This article examines the human concept of the environment and the universe from the point of view of the Qur'an. This study is based on the lack of human concern for the environment. Several verses in the Al-Qur'an emphasize prohibitions and reprisals for those who damage the environment and those who protect it. The research approach is qualitative type of literature. The data sources are literature in the field of environment, Al-Qur'an and Tafseer. Data engineering is carried out with related references, both manually and digitally, especially in the Google Scholar database with the keyword used is the Concept of Humans Against the Environment and the Universe in the Perspective of the Qur'an. The collected data were then analyzed using inductive thinking patterns. The results of the research show that humans and the environment have a relationship where humans as caliphs on earth must always think about what has been bestowed by Allah SWT, so that they are able to make real natural resources, and the creation of the natural environment makes humans always remember the main purpose of being created on earth, namely to pronunciation to Allah SWT.